A History of Sukkot in the Second Temple and Rabbinic Periods - Rubenstein, Jeffrey (Brown Judaic Studies, 2020)
This study analyzes the history of the festival of Sukkot during the second temple and rabbinic periods. While the Jerusalem temple stood, Sukkot was the preeminent festival and primary pilgrimage. The cult observed the festal week with sacrifices, processions, fertility rites and other temple rituals. The destruction of the second temple in 70 CE left rabbinic Judaism with the question of how to celebrate Sukkot, a temple festival, without a temple. Which elements were retained from the legacy of cultic rituals and which were abandoned? What does the rabbinic Sukkot festival share with its antecedent of temple times and in what does it differ? How did Sukkot evolve in the later rabbinic periods as memories of the temple receded? Rubenstein's book address these issues by tracing the development of the festival over the course of a millennium.